Adaptive space-time transmission with side information. - Lo, T. (IEEE Transactions on wireless communications)
In this letter, a simple adaptive transmit diversity technique with side information is presented. The proposed scheme has a number of attractive characteristics. First, it is simple to implement. Second, it is efficient in terms of bandwidth requirements for side information feedback. Finally, it adapts to the quality of the side information to accordingly configure the space-time signal set to be transmitted so that additional gain in signal-to-noise ratio can be achieved at the receiver. In effect, it can be viewed as a flexible combination of suboptimal beamforming and space-time block coding.